Connected component detector using Dormand and Prince algorithm. (1st January 2011) - Senthilkumar, S.
This paper deals with solving system of non-linear differential equation of cellular neural networks (CNNs) using different single-step numerical integration algorithms for connected component detector (CCD) along with bifurcation behaviour. Also, a simple cloning template for CNN is employed to detect the number of connected components of a vector in +1, −1 N . Simulation results demonstrate that sixth order Dormand and Prince algorithm outperforms well in real time processing.